2020
DOI: 10.12973/eu-jer.9.4.1605
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Entrepreneurial Leadership on Students' Entrepreneurial Intentions: Teacherpreneurship as a Mediating Variable

Abstract: <p style="text-align: justify;">The paper aims to know the influence of entrepreneurial leadership on the students' entrepreneurial intentions as well as its impact on teacherpreneurship. The design employed was quantitative with the ex post facto method using Partial Least Square Structural Equation Modelling (PLS-SEM) to test the hypothesis. The samples were taken using a stratified random sampling technique, obtaining 70 teachers and 285 students as the respondents. The data were gathered through a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The results of this study showed that teachers' charismatic leadership has a significant positive impact on college students' entrepreneurial intentions, and the finding is consistent with those of previous studies (Sujana et al, 2022;Suyudi et al, 2020). Sujana et al (2022) conducted a study in college students and found that their entrepreneurial intentions are significantly and positively affected by teachers' transformational leadership.…”
Section: Theoretical Contributionssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study showed that teachers' charismatic leadership has a significant positive impact on college students' entrepreneurial intentions, and the finding is consistent with those of previous studies (Sujana et al, 2022;Suyudi et al, 2020). Sujana et al (2022) conducted a study in college students and found that their entrepreneurial intentions are significantly and positively affected by teachers' transformational leadership.…”
Section: Theoretical Contributionssupporting
confidence: 91%
“…Sujana et al (2022) conducted a study in college students and found that their entrepreneurial intentions are significantly and positively affected by teachers' transformational leadership. Consistent with the finding, Suyudi et al, (2020) found that the principal's entrepreneurial leadership has a significant positive impact on students' entrepreneurial intentions. Unlike previous studies, the present study determined the impact of teachers' charismatic leadership on college students' entrepreneurial intentions.…”
Section: Theoretical Contributionssupporting
confidence: 79%
“…The definition of Entrepreneurial Leadership used has a close relationship with entrepreneurial construction, transformational leadership and leadership that supports creativity (Renko, Tarabishy, Carsrud, & Brannback, 2013). Entrepreneurial Leadership provides entrepreneurial knowledge for teachers and students in creating innovation and creativity in higher education (Suyudi, Suyatno, Rahmatullah, & Rachmawati, 2020).…”
Section: Entrepreneurial Leadershipmentioning
confidence: 99%
“…The goal is to increase entrepreneurial literacy from an early age. Not only that, the role of educational institutions is also very important to sharpen Entrepreneurial Leadership in order to develop creativity and innovation in schools, stimulate the growth of the entrepreneurial spirit of students (Suyudi, Suyatno, Rahmatullah, & Rachmawati, 2020). An entrepreneur who has received business training will have good entrepreneurial literacy so that he can apply the right business processes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the pieces of literature, students' decisions to become entrepreneurs are significantly influenced by their entrepreneurial behavior. In several countries, students are becoming more interested in entrepreneurship or are attempting to establish their businesses rather than working for others and are considering starting a new business as a planned career path (Kirby & Ibrahim, 2011;Suyudi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%